International Benchmarking of Lesotho's Infrastructure Performance - Bogetić, Željko (World Bank, Washington, DC, 2014)
The author provides a preliminary benchmarking of infrastructure performance in Lesotho in four major sectors--electricity, water and sanitation, information and communication technology, and road transportation--against the relevant group of comparator countries using a new World Bank international data base with objective and perception-based indicators of infrastructure performance from over 200 countries. The results of the benchmarking are revealing of several major, comparative deficiencies in infrastructure performance in Lesotho: (1) extremely low access to electricity and its affordability; (2) poor coverage, quality, and the cost of local (non-cellular) telephony; and (3) poor quality of roads. Infrastructure service delivery in electricity, telephony, and roads is well below what would be expected, on average, for a country in Lesotho's income group. In these sectors, Lesotho also compares unfavorably with many other geographical country groups. Unless addressed, such infrastructure shortfalls are likely to adversely affect the welfare of Lesotho's poor, and the cost competitiveness and growth prospects of a range of economic sectors (such as tourism and trade) that depend critically on a stable and competitive supply of basic infrastructure service. They could also affect the speed and quality of Lesotho's regional economic integration within the South Africa Customs Union (SACU) sub-region with attendant consequences for the long-term growth of regional trade and real output. By contrast, Lesotho's performance is solid in the access to improved water and sanitation, in the aggregate and in both rural and urban areas. Finally, this benchmarking, combined with more in-depth, sector analyses, could provide policymakers in Lesotho a useful guide to the areas of infrastructure performance requiring attention.